Pengaruh Dewan Direksi, Kepemilikan, dan Implementasi SDG terhadap Kinerja Keuangan di Sektor Konsumen Non-Siklikal Indonesia - Syntia Feby Berliana; Stefani Dyah Retno Pudyanti; Henny Setyo Lestari; Susy Muchtar (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of board characteristics, ownership attributes, and SDG implementation on corporate financial performance in Indonesia’s consumer non-cyclical sector. The research uses a quantitative approach with secondary data collected from 41 publicly listed companies between 2022 and 2024. Financial and sustainability reports were used as sources, and the data were analyzed using panel data regression. The findings reveal that female board membership and sales growth have a positive impact on long-term capital efficiency (ROCE), while board independence and institutional ownership negatively affect it. Foreign ownership significantly improves short-term profitability (ROA), while SDG implementation shows a trade-off—reducing ROA but enhancing ROCE. Leverage and firm age positively affect ROA but reduce ROCE, whereas firm size shows the opposite pattern. These results underline that governance mechanisms and corporate characteristics have mixed effects on different dimensions of financial performance. The study provides insights for corporate managers to refine governance strategies and for investors to better evaluate firm fundamentals. Future studies are encouraged to include qualitative approaches and cross-sectoral comparisons to broaden the analysis.